Código corretor de erros multi bit upset com dupla verificação - Rohde, Tiago Mallmann (2020)
Major technological advances have been developed, especially in the space field. The CubeSat standard allowed several entities to also participate in the development of these tech- nologies. Thus, the circuits that integrate the most diverse systems have been evolving rapidly and the amount of logical cells within the same physical space increases, that is, the circuits are increasingly dense. In space, cosmic radiation is more intense, causing the errors stemmed from the impact of highly charged particles become increasingly worrying, given that the Er- ror Correcting Codes need to be increasingly effective to ensure the information integrity.This research exposes the development of a double check algorithm, where the bits that check the data are previously checked by other parity bits, in order to mitigate false positives during the process of correcting the bits affected by the Single Event Effect and consequently expand the coverage of upsets errors within the Static Random Access Memmory. The simulations, were developed in MATLAB and were contained in the high level programming, showed that the algorithm has different adjustment rates compared to already established techniques in the sci- entific environment. The coverage of errors was distributed in 97% in a 3X3 radius for all the possibilities, 55% in a 4X4 radius for all possibilities of up to 9 errors and 68,08% of correction contemplating the 90.485.041 simulations that comprise single and multiple impacts of highly charged energy particles.